Breaking the Resource Curse: The Role of Natural Resource Funds - Adeleke, Isaiah; Zubairu, Umaru Mustapha (LPPM of NAROTAMA UNIVERSITY, 2021)
Studies have shown that the paradox of “the more resource-rich the poorer” otherwise known as “resource curse” has been prevalent in many countries endowed with natural resources. To mitigate this trend, a revenue management strategy called Natural Resource Funds (NRFs) - a government owned special-purpose vehicle to ensure effective management of the country’s natural wealth was embraced in some nations. This paper critically reviewed the roles of NRFs in breaking the resource curse. The Systematic Quantitative Assessment Technique (SQAT) was adopted in identifying and reviewing sixty-seven (67) peer reviewed journal articles that had researched on NRFs in the last decade. The findings were that NRFs have played an effective role in some advanced countries (Chile and China), while they have failed, especially in Africa, Middle East and Latin America due to poor institutional framework and governance. A globally set code of resource governance was recommended to strengthen the role of NRFs and enhance their effectiveness. Resource revenue maximization other than revenue utilization would be a good area for future research.